The mobile application hacker's handbook - Chell, Dominic (Indianapolis, IN : John Wiley & Sons, 2015)
This is a comprehensive guide to securing all mobile applications by approaching the issue from a hacker's point of view. It provides expert guidance toward discovering and exploiting flaws in mobile applications on the iOS, Android, Blackberry, and Windows Phone platforms. You will learn a proven methodology for approaching mobile application assessments, and the techniques used to prevent, disrupt, and remediate the various types of attacks. Coverage includes data storage, cryptography, transport layers, data leakage, injection attacks, runtime manipulation, security controls, and cross-platform apps, with vulnerabilities highlighted and detailed information on the methods hackers use to get around standard security. --
Mobile application (in)security -- Analyzing IOS applications -- Attacking IOS applications -- Identifying IOS implementation insecurities -- Writing secure IOS applications -- Analyzing Android applications -- Attacking Android applications -- Identifying and exploiting Android implementation issues -- Writing secure Android applications -- Analyzing Windows Phone applications -- Attacking Windows Phone applications -- Identifying Windows Phone implementation issues -- Writing secure Windows Phone applications -- Analyzing BlackBerry applications -- Attacking BlackBerry applications -- Identifying BlackBerry application issues -- Writing secure BlackBerry applications -- Cross-platform mobile applications.
Includes index.
Description based on print version record.
Keywords: Mobile computing; Mobile apps; Hacking; Electronic books; Electronic books